The rabbis and the prophets - Neusner, Jacob, 1932-2016 (Studies in Judaism., 2011)
This book shows how the Rabbis of late antiquity took over writings from what they recognized as ancient times and of divine origin and they re-presented selections of those writings in accord with their own project_s requirements, glossing clauses of the prophetic Scriptures but not whole, propositional discourses.